The Combination of Fasting, Acute Resistance Exercise, and Protein Ingestion Led to Different Responses of Autophagy Markers in Gastrocnemius and Liver Samples - Pinto, Ana P.; Vieira, Tales S. [UNESP]; Marafon, Bruno B.; Batitucci, Gabriela [UNESP]; Cabrera, Elisa M. B.; Rocha, Alisson L. da; Kohama, Eike B.; Rodrigues, Kellen C. C.; Moura, Leandro P. de; Pauli, Jose R.; Cintra, Dennys E.; Ropelle, Eduardo R.; et al. (Mdpi, 2020)
The present study verified the responses of proteins related to the autophagy pathway after 10 h of fast with resistance exercise and protein ingestion in skeletal muscle and liver samples. The rats were distributed into five experimental groups: control (CT; sedentary and without gavage after fast), exercise immediately (EXE-imm; after fast, rats were submitted to the resistance protocol and received water by gavage immediately after exercise), exercise after 1 h (EXE-1h; after fast, rats were submitted to the resistance protocol and received water by gavage 1 h after exercise), exercise and supplementation immediately after exercise (EXE/Suppl-imm; after fast, rats were submitted to the resistance protocol and received a mix of casein: whey protein 1:1 (w/w) by gavage immediately after exercise), exercise and supplementation 1 h after exercise (EXE/Suppl-1h; after fast, rats were submitted to the resistance protocol and received a mix of casein: whey protein 1:1 (w/w) by gavage 1 h after exercise). In summary, the current findings show that the combination of fasting, acute resistance exercise, and protein blend ingestion (immediately or 1 h after the exercise stimulus) increased the serum levels of leucine, insulin, and glucose, as well as the autophagy protein contents in skeletal muscle, but decreased other proteins related to the autophagic pathway in the liver. These results deserve further mechanistic investigations since athletes are combining fasting with physical exercise to enhance health and performance outcomes.
Keywords: resistance exercise; autophagy; leucine; mammalian target of rapamycin (mTOR); liver; muscle